The influence of microbiome‐derived amino acids metabolites in shaping the glioma immunosuppressive microenvironment - Qianquan Ma; Zhihao Song; Chenlong Yang; Zijin Zhao; Guodong Tang; Jia You; Chong Zeng; Jun Yang; Qing Liu; Haoyu Li; Wei Huang (Interdisciplinary Medicine)
Abstract Gliomas are the most common intracranial tumors characterized by highly malignant behavior. In addition to genetic and epigenetic mutations, the unique cancer microenvironment (CME) plays a pivotal role in glioma progression and resistance to therapy. Among the critical factors in the glioma CME, amino acid metabolism stands out for its significant influence, with specific amino acids suppressing anti‐cancer immune responses and promoting an immunosuppressive environment. The human microbiota affect host metabolism and immune functions, with disruptions in microbiota homeostasis leading to metabolic alterations and immune dysfunction in various diseases. Emerging evidence highlights the role of microbiota‐derived metabolites, including amino acids, in reprogramming the glioma CME and modulating oncogenic signaling pathways. This review examines the influence of the gut microbiome on specific amino acid metabolism—namely, tryptophan, tyrosine, arginine, and branched‐chain amino acids—and evaluates the potential roles of microbiome‐derived metabolites in the prognosis and diagnosis of glioma.